PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Perusahaan Sektor Pertambangan dan Pertanian yang Terdaftar Di Bursa Efek Tahun 2012-2014) - Harisianto, Rachmat; Sutjahyani, Dewi (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTThis research was conducted to analyze the effect of Corporate Social Responsibility performance indicators Economic, Environmental, and Social on financial performance. This study was made to determine how the implementation of Corporate Social Responsibility Financial Performance. The method used in this research is quantitative method and the population is a company mining and agricultural sectors listed in Indonesia Stock Exchange in 2012-2014, using data analysis SEM (Structural Equation Modelling) by the application program PLS (Partial Least Square) version 3.2. 1. Results obtained indicate that Corporate Social Responsibility (CSR) of the three indicators Economic Performance (KE), Environmental Performance (KL), Social Performance (KS) to the company's financial performance and Agriculture Mining sector not significant coefficient -0317 parameter Corporate social yangberarti responsibility (CSR) to the financial performance had a negative relationship which means no direction opposite relationship. Keywords: Influence of Corporate Social Responsibility of the three indicators Economic Performance, Environmental, and Social the Financial Performance.